Ovidian intertextuality and metamorphosis in Prudentius - Philip Hardie (Dictynna)
Richard Bentley famously called Prudentius ‘Christianorum Maro et Flaccus’. Recent work has explored the extent and detail of Prudentius’ Virgilian intertextuality, most notably in the allegorical epic the Psychomachia, but also in many others of his works. Horatian lyric is laid under contribution not just in the lyric metres of the hymns in the Cathemerinon. The personal Praefatio and Epilogus allude mostly to Horace, and hardly at all to Virgil (not surprising, given Horace’s use of first-person genres in autobiographical mode). In this paper I focus on allusion to a poet arguably almost as important for Prudentius as Virgil and Horace, Ovid. In particular, I look at Prudentius’ allusion to the themes and language of Ovidian metamorphosis.